2019
DOI: 10.32098/mltj.02.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative elastography of Achilles tendon using Shear Wave Elastography (SWE): correlation with zonal anatomy

Abstract: Introduction:To evaluate the feasibility and reproducibility of quantitative ultrasonic measurement of normal Achilles tendon (AT) stiffness, using supersonic shear wave elastography (SWE) in correlation with its zonal anatomy. Materials and methods: Thirty tendons (8 women, 7 men) (mean age, 29,5 years; age range, 24-51 years) underwent morphologic and SWE measurements. The quantitative measurements of the tendon in four points (musculo-tendinous junction, tendinous body, pre-insertional area and enthesis) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…A comparative study utilising shear wave elastography (SWE) of four zones (musculo-tendinous junction, body, pre-insertional and enthesis) of the Achilles tendon complex with the foot dorsiflexed and planatarflexed have indicated comparative findings to our study (36). Petitpierre et al 2018 (36) found stiffness in the Achilles complex increased from its musculo-tendinous junction to its enthesis. Even though the study sample size was smaller than ours, the results support the findings of our study adding weight to the case for tendon assessment loaded and unloaded.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A comparative study utilising shear wave elastography (SWE) of four zones (musculo-tendinous junction, body, pre-insertional and enthesis) of the Achilles tendon complex with the foot dorsiflexed and planatarflexed have indicated comparative findings to our study (36). Petitpierre et al 2018 (36) found stiffness in the Achilles complex increased from its musculo-tendinous junction to its enthesis. Even though the study sample size was smaller than ours, the results support the findings of our study adding weight to the case for tendon assessment loaded and unloaded.…”
Section: Discussionsupporting
confidence: 62%
“…Where previously too much stiffness has been associated with bony injuries and too little stiffness with soft tissue injuries (34,35). A comparative study utilising shear wave elastography (SWE) of four zones (musculo-tendinous junction, body, pre-insertional and enthesis) of the Achilles tendon complex with the foot dorsiflexed and planatarflexed have indicated comparative findings to our study (36). Petitpierre et al 2018 (36) found stiffness in the Achilles complex increased from its musculo-tendinous junction to its enthesis.…”
Section: Discussionmentioning
confidence: 53%
“…The reason of that choice relies on the fact that some authors suggest collecting shear wave elastography measurements in m/s since in anisotropic tissues (as tendons) shear waves velocity may not exactly correspond to the Young Modulus, 11 but many studies were performed using the only kPa as measure unit to assess human calcaneal tendon elasticity. 22,24 Since in veterinary medicine, there are no available data about the application of this technique on tendons, in this study, measurements have been collected with both measurement units and these preliminary results suggest that kPa seems to be slightly more reproducible than m/s. About intra-observer repeatability, this was considered excellent for both operators in each common calcaneal tendon portion examined, thus providing that the single measurements are highly repeatable.…”
Section: Discussionmentioning
confidence: 74%
“…These data are coherent to what is described in human medicine about calcaneal tendon elasticity; Petitpierre and colleagues described the same results in their study, assessing that this could be explained by the histological tendon structure which is different from different sections of the same tendon. 22 Physiologically a tendon is composed of collagen fibres and striated muscle fibres smaller quantities than in muscle in its musculotendinous junction, 30 while the healthy body and the pre-insertional portion are characterized by type 1 collagen and a few elastic fibres in a ground substance with cells and water. The enthesis is, on the contrary, characterized by the presence of fibrocartilage, 31 thus explaining the progressive increase of stiffness from the musculotendinous junction to the tendon enthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation